Exceptional combinations of tensile properties and corrosion resistance in a single-phase Ti1.6ZrNbMo0.35 refractory high-entropy alloy - Wang, Hao; Chen, Weiping; Liu, Shiyu; Chu, Chenliang; Huang, Liran; Duan, Jiaqi; Tian, Zhao; Fu, Zhiqiang (Intermetallics, 2024)
In this study, we introduce a novel single-phase Ti1·6ZrNbMo0.35 refractory high-entropy alloy (RHEA), synthesized through vacuum arc-melting. The as-cast RHEA demonstrates excellent mechanical properties with a high yield strength of ∼930 MPa and a large tensile strain of ∼15.4 %, achieved through severe lattice distortion. Moreover, our investigation reveals the superior corrosion resistance of the RHEA in 3.5 wt% NaCl solution. The remarkable anti-corrosion properties are attributed to the single-phase structure, the increase of Mo6+ oxides in the passive film and continuous passive oxidation of the elements. This work provides a new and significant approach to designing novel RHEAs with excellent combinations of strength-ductility synergy and superior corrosion resistance. [Display omitted] •Ti1·6ZrNbMo0.35 RHEA with a single-phase BCC structure was successfully developed and fabricated.•The as-cast RHEA shows a high tensile yield strength of ∼930 MPa and a large fracture strain of ∼15.4 %.•The as-cast RHEA shows excellent corrosion resistance in 3.5 wt% NaCl solution.•Excellent combinations of mechanical properties and corrosion resistance in RHEA was achieved.